2020
DOI: 10.3390/cells9010153
|View full text |Cite
|
Sign up to set email alerts
|

Network of Interactions between ZIKA Virus Non-Structural Proteins and Human Host Proteins

Abstract: The Zika virus (ZIKV) is a mosquito-borne Flavivirus and can be transmitted through an infected mosquito bite or through human-to-human interaction by sexual activity, blood transfusion, breastfeeding, or perinatal exposure. After the 2015–2016 outbreak in Brazil, a strong link between ZIKV infection and microcephaly emerged. ZIKV specifically targets human neural progenitor cells, suggesting that proteins encoded by ZIKV bind and inactivate host cell proteins, leading to microcephaly. Here, we present a syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Prior studies designed to identify and confirm cellular targets of Zika protease commonly utilize a well-characterized chimera fusion between a soluble loop from NS2B transmembrane component and the NS3 protease domain that expresses as a soluble active protease in cells (Yamaoka et al, 2021;De Jesú s-Gonzá lez et al, 2020;Li et al, 2019;Hill et al, 2018;Coyaud et al, 2018;Shah et al, 2018;Scaturro et al, 2018). More recent proteomic analyses expressed the NS3 component in the absence of the NS2B subunit (Golubeva et al, 2020;Coyaud et al, 2018). In our hands, the NS2B-NS3 chimera, s-ZPrC, exhibited toxicity in cells and cell death of the majority of transfected cells, similar to that observed in previous reports (not shown) (Arias-Arias et al, 2020;Li et al, 2019).…”
Section: Zika-encoded Protease Readily Cleaves Sites Within the Motor Domain Of Hseg5mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies designed to identify and confirm cellular targets of Zika protease commonly utilize a well-characterized chimera fusion between a soluble loop from NS2B transmembrane component and the NS3 protease domain that expresses as a soluble active protease in cells (Yamaoka et al, 2021;De Jesú s-Gonzá lez et al, 2020;Li et al, 2019;Hill et al, 2018;Coyaud et al, 2018;Shah et al, 2018;Scaturro et al, 2018). More recent proteomic analyses expressed the NS3 component in the absence of the NS2B subunit (Golubeva et al, 2020;Coyaud et al, 2018). In our hands, the NS2B-NS3 chimera, s-ZPrC, exhibited toxicity in cells and cell death of the majority of transfected cells, similar to that observed in previous reports (not shown) (Arias-Arias et al, 2020;Li et al, 2019).…”
Section: Zika-encoded Protease Readily Cleaves Sites Within the Motor Domain Of Hseg5mentioning
confidence: 99%
“…Viral proteins directly interact with cellular components, via protein-protein interactions, to exert this control. In the case of Zika, with its limited proteome, the NS2B-NS3 protease is known to cleave host proteins (Golubeva et al, 2020;Hill et al, 2018;Coyaud et al, 2018;Shah et al, 2018;Scaturro et al, 2018), whereas both the NS4 and NS5 proteins collaborate to inhibit the establishment of cellular antiviral state by blocking the interferon (IFN)-a/b pathway (Liang et al, 2016;Dar et al, 2017;Grant et al, 2016;Kumar et al, 2016). Numerous recent studies have documented that Zika virus can impair neurogenesis and interfere with the proliferation of neuronal precursor cells (Ferreira and Garcez, natively ER membrane bound by NS2B, but with a C-terminal truncation in NS3 that removes the helicase domain.…”
Section: Introductionmentioning
confidence: 99%
“…There are many real bipartite networks such as actor-movie network [35] which illustrates the movies and the actors playing in them, author-article network [36] which shows the articles and theirs authors, gene-disease network [37][38][39][40][41][42][43] which reveals diseases and their targeted genes, metabolite-enzyme network [44][45][46] which shows metabolites and their corresponding enzymes, and host-pathogen PPI network such as fungal pathogen scedosporium aurantiacum with human long epithelial cells [47], Leptospira interrogans and Homo sapiens [48], extracellular bacterial pathogen and human host [49], zika virus non-structural proteins and human host proteins [50], bacterial and fungal pathogens and maize stalks host [51].…”
Section: Preliminaries and Definitionsmentioning
confidence: 99%
“…These pathways may be crucial in understanding ZIKV infection and subsequent microcephaly in foetuses. Recent proteomics studies exploring the ZIKV-host interactome have identified, amongst an extensive array of cellular targets, networks associated with signalling and mitotic pathways [27][28][29][30]. For example, Golubeva et al identify shared interactions with 14 of the reported MCPH-related genes [30].…”
mentioning
confidence: 99%